Effects of silicon-rich soil amendments on growth, mortality and bark feeding damage of Sitka spruce (Picea sitchensis) seedlings under field conditions. Issue 6 (18th August 2018) - Hogan, Brian; McDermott, Frank; Schmidt, Olaf
ABSTRACT: Alternative methods of protection are required against feeding by the large pine weevil ( Hylobius abietis ) on the bark of conifer seedlings. Silicon (Si) has been shown to enhance the resistance of plants to insect herbivores. This study investigated the effects of low doses of Si-rich soil amendments on growth, mortality and bark feeding damage of Sitka spruce ( Picea sitchensis ) seedlings. Two-year old seedlings were grown, individually, in soil taken from a tree nursery treated with coal ash, peat ash, rice husk ash, slag, sodium metasilicate or a commercially available Si fertiliser (Pro-Tekt) and planted out on two reforestation sites in Ireland. Seedlings grew well (about 20% growth in terms of height, 66% in root collar diameter, after two growing seasons), and Si-rich amendments did not have a significant effect on growth or mortality. Bark feeding damage on Si-treated seedlings did not vary significantly from control seedlings. Bark Si concentrations were not significantly larger in treated seedlings than in control seedlings, but control seedlings already had comparatively high bark Si concentrations (560 mg kg −1 dry tissue). In conclusion, Sitka spruce seedlings grown in the presence of Si-rich soil amendments prior to planting did not show greater resistance to weevil feeding under the present conditions.